A COMPARATIVE STUDY ON THE LEVEL OF AGGRESSIVITY OF ATHLETES PRACTICING JU-JITSU AND NON-PRACTITIONERS (GYMNASIUM, 2017)
Aggressivity represents one of the daily problems of the XXI century. The present study aims to analyze the level of aggressivity of two study groups made up of subjects aged between 15 and 18 years: one group includes performance athletes from Martial Arts Club Budo Seishin and the other one non-practitioners from Alexandru Vlahuță Highschool. Martial arts and ju-jitsu in particular can influence the level of aggressivity of the subjects in a positive manner, helping relieve stress and frustrations. Having knowledge about these elements can provide information about the level of aggressivity of the subjects and we will verify whether ju-jitsu represents a solution to help interested people in constructively directing aggressivity. Our findings indicate an increased level of physical, verbal aggressivity and hostility in non-practitioners rather than in sportsmen, which validates the research hypothesis.